(untitled) (Research, Society and Development, 2021)
Platelet Concentrates (PCs), such as Platelet Rich Fibrin (PRF), are used to improve wound healing. One of the surgical procedures where this material is most used is in maxillary sinus floor augmentation surgery. PRF can assist the regeneration of hard and soft tissues, be used alone or with other biomaterials and prevent and treat Schneider membrane perforation. The aim of this study was to review the literature on PRF and its applications in maxillary sinus floor surgery. A search for articles was carried out, in English, using a LILACS, Pubmed e Google Scholar databases, from 2006 to 2021. Clinical trials, literature reviews and systematic reviews were included. PRF proved to be an easy, simple and economical method of assisting tissue repair. It can assist in the correction of bone height deficiencies, complementing and positively assisting maxillary sinus floor augmentation surgery. However, there is a lack of consensus regarding the effective contribution of PRF to maxillary sinus floor augmentation surgery. Thus, more randomized studies using the same protocol for obtaining this platelet concentrate are needed.